Laboratory Inventory System - Hashim, Nik Mohd Zarifie; Mohd Arifin, Nor Azereen Mahmudah (IJSR, 2013)
There are a lot of forms to be completed as the inventory process happened. Many systems had been introduced to manage and place the inventory items to be in a systematic ways. The proposed project was about laboratory inventory that will be used as a system at Faculty of Electronics and Computer Engineering (FKEKK). The project will be known as the Laboratory Inventory System (LIS). This system focused on recording and updating the data. It is also have a report in the system which will make user easier to check the current status of the each equipment and component in the laboratory. Besides, this system development was based on forms oriented that were used by the technicians and staffs before. This new system also used database concept to store all the information which related with land application processes. The methodology which has been used to guide this project development is RAD (Rapid Application Design) methodology. The problem of the current system of the Laboratory Inventory System (LIS) had been analyzed and from that, requirement analysis had been made. The results show that the main objective to develop the fully functional software that fulfills all the criteria needed is successfully achieved. This system is